2017
DOI: 10.1080/02755947.2017.1296515
|View full text |Cite
|
Sign up to set email alerts
|

Black Bass Dispersal Patterns Following Catch‐and‐Release Tournaments on Lake Champlain

Abstract: Lake Champlain is consistently ranked as one of the top fisheries for black bass Micropterus spp. in the United States. Tournament fishing on the lake has become increasingly popular, with dozens of tournaments held annually since the early 2000s and at least 60 more planned for 2017. The largest of these tournaments launch from Plattsburgh, New York, and their frequency has generated concerns among fishery managers and the public over post‐weigh‐in mortality and stockpiling. However, relatively little is know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Based on the information obtained for the frequency of impacts provided by our experiments, it is likely that travel distances similar to those reported by anglers in our surveys, as well as in Maynard et al. (), would be associated with several hundred impacts between the fish and the walls of the live well during the tournament day.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Based on the information obtained for the frequency of impacts provided by our experiments, it is likely that travel distances similar to those reported by anglers in our surveys, as well as in Maynard et al. (), would be associated with several hundred impacts between the fish and the walls of the live well during the tournament day.…”
Section: Discussionsupporting
confidence: 78%
“…According to Maynard et al. (), anglers involved in tournaments on Lake Champlain commonly travel over 100 km from sites where fish are caught to the weigh‐in site. The results of surveys conducted in the present study showed that long travel distances are also common for bass tournament anglers on Lake Ontario.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations